Decoding the Role of Gender in the Relationship Between the Online Payment System and SME Performance: A Case Study Investigating an Emerging Economy—Bangladesh - Nahar, Sharmin (Frontiers in Research Metrics and Analytics, 2022)
This research examines the moderating role of gender on the adoption of online payment systems (OPS). It also explores the impact of using OPS on the performance of SMEs in an emerging economy, using the Technology Acceptance Model (TAM) and Resource-Based View (RBV). The results indicate that male SME owners (entrepreneurs) are more likely to focus on perceived usefulness, whereas female SME entrepreneurs are more likely to focus on perceived ease of use while adopting OPS, according to data obtained from 302 SMEs in Bangladesh through face-to-face surveys. The results also report that the use of OPS has a considerable positive effect on SMEs' performance. The study's findings will add to the scarce research on the impact of using OPS on business performance in the context of SMEs in emerging economies, in addition to enhancing the OPS adoption literature from a gendered lens.